From Cairo to Christ: how one Muslim's faith journey shows the way for others - Atallah, Abu (IVP Books, an imprint of InterVarsity Press, 2017)
A kid in Cairo -- Adolescence in an Arab family -- Encountering Christ -- A frightened new Christian -- In the United States -- Ministry in the United States -- Arabs and the West -- In Europe -- Misunderstandings in Europe -- Christians in Egypt -- Israel and the Muslims -- Marriage and family in Islam -- Christian-Muslim families -- Egypt now -- Muslim converts -- Current ministry